A Sea of Unspoken Things : A Novel - Young, Adrienne, 1985- ([New York : Delacorte Press, 2025)
"In this captivating atmospheric novel from the New York Times bestselling author of The Unmaking of June Farrow, a woman investigates her twin brother's mysterious death while confronting the ghosts of her own haunted past"--Provided by publisher.
new book 2025 winter.
Keywords: Brothers -- Death -- Fiction; Accidents -- Fiction; Family secrets -- Fiction; Twins -- Fiction; Mystery & Detective; Siblings; Family life; Thrillers; California -- Fiction; Novels; Detective and mystery fiction; Detective fiction; Mystery fiction